Health Tracker - Arkan Nezam Fares; Mohammed Najeh Abdullrazeq (My University, 2026)
Health Tracker is a cross-platform mobile healthcare management system designed to help users store and understand their medical information, track medications, and receive AI-assisted explanations of laboratory reports and symptoms. The system consists of a React Native (Expo) mobile application and a Laravel REST API backend integrated with cloud services and multiple AI providers. Lab reports can be uploaded as PDFs or images; the backend stores the files in AWS S3, prepares AI prompts, and retrieves structured medical findings in JSON format. The mobile application presents the extracted results in a patient-friendly form and provides additional features such as medication scheduling with reminders, health profile management, and an AI Doctor consultation module that supports text and optional image inputs. The project emphasizes security, modularity, and extensibility through token-based authentication, clean service abstractions, and clear separation between client, API, data, and AI processing layers. The implemented system demonstrates a practical architecture for integrating modern AI services into a healthcare-oriented application while preserving maintainability and future upgrade paths.